Comparison of Manikin Versus Porcine Trachea Models When Teaching Emergent Cricothyroidotomy Among Emergency Medicine Residents. Issue 3 (7th April 2019) - Gustafson, Mark L.; Hensley, Brian; Dotson, Marc; Broce, Mike; Tager, Alfred
Abstract: Objectives: Emergent cricothyroidotomy (EC) is a rarely used yet lifesaving procedure that is important for an emergency physician to master throughout his or her training. We evaluated the difference in utilization of a manikin or porcine model among emergency medicine (EM) residents when teaching EC. We also evaluated the difference in the models using two different commonly utilized and taught techniques: "scalpel‐finger‐bougie" (SFB) technique and the Melker technique (MT). Methods: This was a prospective crossover design. Instructions about the procedure were provided; study participants were randomly assigned to one of two groups and performed cricothyrotomy on both manikin and porcine simulators using both the Melker and the SFB techniques. Each group was started with the technique on the second simulator opposite what they started with on the first simulator. After the procedures, study participants completed a questionnaire that used the same format for both groups. All survey questions required a 7‐point Likert scale response. Confidence, difficulty, reality of the anatomy, and landmarks were compared. Results: Fifteen EM residents participated in the study. Compared to the porcine‐first group, the manikin‐first group rated the anatomy more realistic (question 5) after their first attempt (6.29 vs. 5.87) than their second attempt (using the porcine model; 4.29 vs. 5.62; main effect for attempts [first vs. second] p = 0.027; interaction p = 0.074). Interestingly, the porcine model–first group rated the landmarks (question 6) significantly easier to find in both attempts (6.87 vs. 5.86 on the first attempt and 6.50 vs. 5.57 on the second attempt; p = 0.012). Twelve participants (80%) chose SFB as their preferred technique to use in real‐life scenario. Conclusion: The Manikin model tends to be more realistic in cricothyrotomy simulation than the porcine model. The influence of fresh pig skin overlying the porcine model may require further research. Landmark identification during the procedure was easier on both models when participants start with the porcine model. Participants prefer the SFB over MT if faced with a real‐life scenario.